2018
DOI: 10.11158/saa.23.2.16
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Tyrophagus putrescentiae (Acaride) to odour associated with its predator Neoseiulus cucumeris (Phytoseiidae) 

Abstract: This study is the first of a series of experiments on the non-consumptive effects of N. cucumeris on the behaviour and life history parameters of T. putrescentiae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Neoseiulus cucumeris is a common predator of T. putrescentiae (Lee et al 2020) and was used as the predator to exert predation stress in this study (Wei and Zhang 2019). A previous study already showed in a two-choice test that T. putrescentiae preferred the cell not previously exposed to its predator N. cucumeris, which indicates that T. putrescentiae could respond to the cues deposited by its predator N. cucumeris (Wei and Zhang 2018). Later, Wei and Zhang (2019) designed a modified setup consisting of two Munger cells separated by a screen for T. putrescentiae and N. cucumeris respectively.…”
Section: Introductionmentioning
confidence: 73%
“…Neoseiulus cucumeris is a common predator of T. putrescentiae (Lee et al 2020) and was used as the predator to exert predation stress in this study (Wei and Zhang 2019). A previous study already showed in a two-choice test that T. putrescentiae preferred the cell not previously exposed to its predator N. cucumeris, which indicates that T. putrescentiae could respond to the cues deposited by its predator N. cucumeris (Wei and Zhang 2018). Later, Wei and Zhang (2019) designed a modified setup consisting of two Munger cells separated by a screen for T. putrescentiae and N. cucumeris respectively.…”
Section: Introductionmentioning
confidence: 73%